Ozenoxacin 1% cream in the treatment of impetigo: a multicenter, randomized, placebo- and retapamulin-controlled clinical trial. (September 2014) - Gropper, Savion; Albareda, Nuria; Chelius, Klaus; Kruger, Dawie; Mitha, Ismail; Vahed, Yacoob; Gani, Mashra; García-Alonso, Fernando
ABSTRACT : Aim: We compared the efficacy and safety of ozenoxacin (a new nonfluorinated quinolone) 1% cream with placebo in the treatment of impetigo.Patients & methods: In a randomized, double-blind, multicenter study, patients received ozenoxacin cream or placebo cream twice daily for 5 days (a third group received retapamulin 1% ointment as a control). Clinical, microbiological and laboratory evaluations were performed during follow-up (over 2 weeks).Results: Ozenoxacin was superior to placebo (success rate 34.8 vs 19.2%; p = 0.003). Microbiological success was 70.8% for ozenoxacin and 38.2% for placebo after 3–4 days and 79.2% versus 56.6% after 6–7 days. Ozenoxacin produced more rapid microbiological clearance than retapamulin. All treatments were well tolerated.Conclusion: Ozenoxacin 1% cream was effective and safe in the treatment of impetigo.